Use of exercise testing in the evaluation of interventional efficacy: an official ERS statement. Issue 2 (21st January 2016) - Puente-Maestu, Luis; Palange, Paolo; Casaburi, Richard; Laveneziana, Pierantonio; Maltais, François; Neder, J. Alberto; O'Donnell, Denis E.; Onorati, Paolo; Porszasz, Janos; Rabinovich, Roberto; Rossiter, Harry B.; Singh, Sally; et al.
This document reviews 1) the measurement properties of commonly used exercise tests in patients with chronic respiratory diseases and 2) published studies on their utilty and/or evaluation obtained from MEDLINE and Cochrane Library searches between 1990 and March 2015. Exercise tests are reliable and consistently responsive to rehabilitative and pharmacological interventions. Thresholds for clinically important changes in performance are available for several tests. In pulmonary arterial hypertension, the 6-min walk test (6MWT), peak oxygen uptake and ventilation/carbon dioxide output indices appear to be the variables most responsive to vasodilators. While bronchodilators do not always show clinically relevant effects in chronic obstructive pulmonary disease, high-intensity constant work-rate (endurance) tests (CWRET) are considerably more responsive than incremental exercise tests and 6MWTs. High-intensity CWRETs need to be standardised to reduce interindividual variability. Additional physiological information and responsiveness can be obtained from isotime measurements, particularly of inspiratory capacity and dyspnoea. Less evidence is available for the endurance shuttle walk test. Although the incremental shuttle walk test and 6MWT are reliable and less expensive than cardiopulmonary exercise testing, two repetitions are needed at baseline. All exercise tests are safe when recommended precautions are followed, with evidence suggesting that no test is safer than others. A review of exercise testing to evaluate interventions aimed to improve exercise tolerance in respiratory patients http://ow.ly/U37mQ